To Evaluate the Efficacy of Kutaja Ksharasutra in the Management of Bhagandara w.s.r to Fistula-In-Ano - Sharma, Anjana (International Research Journal of Ayurveda & Yoga, 2023)
Background: Bhagandara has been described as one of the eight grave diseases by Acharya Sushruta which is difficult to cure. ‘Fistula-in-ano is an abnormal hollow tract lined by unhealthy granulation tissue and that connects primary opening inside the anal canal to a secondary opening in the perianal skin. Methods: diagnosed cases of Bhagandara of age groups of 18-70 years of either sex are selected. Ksharasutra treatment is given for the period of 3 months and patients will be observed up to complete healing of fistula tract or 3 months whichever is earlier. Observations And Results: the results of Kutaja Ksharasutra on criteria like pain, discharge ,itching, burning sensation were found statistically highly significant after cutting through tract. Mean U.C.T was found 8.86 approx 9 days. Conclusion: Kutaja Ksharasutra can be considered best because of more acceptability, easily availability, reduction in U.C.T &better wound healing property.